Intra-articular Hematoma Block Compared to Procedural Sedation for Closed Reduction of Ankle Fractures. (October 2018) - MacCormick, Lauren M.; Baynard, Taurean; Williams, Benjamin R.; Vang, Sandy; Xi, Min; Lafferty, Paul
Background: Initial treatment for a displaced ankle fracture is closed reduction and splinting. This is typically performed in conjunction with either an intra-articular hematoma block (IAHB) or procedural sedation (PS) to assist with pain control. The purpose of this study was to compare the safety of IAHB to PS and evaluate the efficiency and efficacy for each method. Methods: A retrospective chart review for ankle fractures requiring manipulation was performed for patients seen in a level I trauma center from 2005 to 2016. The primary outcome was rate of successful reduction. Several secondary outcome measures were defined: reduction attempts, time until successful reduction, time spent in the emergency department (ED), rate of hospital admission, and adverse events. The analysis included 221 patients who received IAHB and 114 patients who received PS. Results: The demographics between the 2 groups were similar, with the exception that more patients with a dislocation received PS, which prompted a subgroup analysis. This analysis demonstrated that patients with an ankle fracture and associated tibiotalar joint subluxation underwent closed reduction in a shorter period of time with the use of an IAHB compared with those receiving PS. In patients sustaining a tibiotalar fracture dislocation, patients receiving PS were successfully reduced with 1 reduction attempt more frequently than those receiving IAHB. Orthopedic surgeons also had higher rates of success on first attempt compared with ED providers. Conclusion: Both IAHB and PS were excellent options for analgesia that resulted in high rates of successful closed reduction of ankle fractures with adequate safety. IAHB can be considered a first-line agent for patients with an ankle fracture and associated joint subluxation. Level of Evidence: Level III, retrospective comparative series.